Proximal interruption of the pulmonary artery: A review of radiological findings - Zhang, Ming-Jie; Cao, Ya-Xian; Zhou, Ning; Wang, Rui; Wu, Hui-Ying; Zhang, Xiao-Chun (Frontiers in Pediatrics, 2022)
Objectives: The proximal interruption of the pulmonary artery (PIPA) has various clinical manifestations. In this review, we are focusing on and summarizing the clinical and radiological features of the PIPA based on relevant literatures. Methods: We have included a total of 25 cases with PIPA in the Guangzhou Women and Children's Medical Center between January 2015 and December 2021. The conventional chest photographs and chest CT angiography (CCTA) of the PIPA patient were analyzed and summarized. Results: The radiological results showed that 17 cases were right PIPA and 8 cases was left PIPA. Besides, the percentage of pulmonary hypoplasia in the affected side was 44%, 36% for pulmonary hypertension, 28% for mosaic sign, 20% for subpleural cystic lucency shadow, 20% for subpleural serrated shadow, 20% for collateral vessel thickening, 16% for subpleural band-like parenchyma, 12% for pneumonia, and 56% for patent ductus arteriosus. Conclusion: PIPA’s clinical manifestations are not specific. Awareness of this anomaly based on radiological manifestations, especially the CCTA manifestations is important in order to rule out alternative diagnoses and allow appropriate management.